BitterSweet - Bercovici, Luca, 1957-; Angie, Everhart; James Russo; Eric Roberts; Brian Wimmer; Joe Penny; Francia Dimase; Lenny Citrano; Joanne Baron; Tom Billett; Carl Ciarfalio; John Snyder; et al. (USA Dog Ate My Script Inc., 1999)
Samantha (Angie Everhart) has a bright career ahead of her until her boyfriend tricks her into helping him with a burglary that turns to murder. Sam takes the rap, and when she gets out of jail four years later, her life in tatters, she's looking for revenge. Turns out her boyfriend's joined the mob and there's a maverick cop (James Russo) who's going to force her to help him get the Big Boss. The dialog is lame and the plot is ludicrous in this direct-to-video distaff variation on Payback. It's the sort of movie in which Angie sneaks off and shoots a buncha bad guys, so the cop threatens to throw her in jail. She sneaks off again--bang, bang, bang--he threatens to throw her in jail again. This goes on three or four times. Former supermodel Everhart skulks and scowls her way through the picture, but even her greased-up hair and grunged-down outfit can't hide those glorious cheekbones. Eric Roberts phones in another one for the paycheck. Only Joe Penny, as a mid-level mobster, brings any life to the party. All that being said, the film works on its most fundamental level--as the story of a woman grimly seeking revenge because it's the only meaningful response to what life has dealt her
Languages: English , Turkish Subtitle: Turkish
Keywords: Thriller